Correlation between mandibular length and third molar maturation based on their radiography appearances - Pramatika, Berty; Azhari, Azhari; Epsilawati, Lusi (Padjadjaran Journal of Dentistry, 2018)
Introduction: Growth and development is a dynamic process that is influenced by many factors, this is why children of the same age do not have the same growth rate, therefore growth can not Â be evaluated only by chronological age, but also by maturation skeletal and dental. Previous research has shown a strong relationship between mandibular length and Cervical Vertebral Maturation (CVM). The aim of the present study was to determine the correlation between mandibular length and mandibular third molar maturation using panoramic radiograph. Methods: This research is an observational analytic cross sectional study. Total 412 panoramic radiographs of 207 male and 205 female aged 9-25 years were evaluated. The mandibular length measured from the point of condylion (Co) to menton (Me). M3 maturation of the mandible was evaluated by Demirjian methods. Results: Spearman non-parametric correlation was used for analysis. A strong correlation was found between mandibular length and third molar development (in males: r=0.705 on the right side and are=0.729 on the left side; in females: are=0.755 on the right side and are=0.707 on the left side) Conclusion: There is a strong correlation between mandibular length and mandibular third molar maturation in both male and female.